2021
DOI: 10.1029/2021ea001859
|View full text |Cite
|
Sign up to set email alerts
|

PBL Height From AIRS, GPS RO, and MERRA‐2 Products in NASA GES DISC and Their 10‐Year Seasonal Mean Intercomparison

Abstract: The planetary boundary layer (PBL), also called the atmospheric boundary layer, is the near-surface section of the atmosphere. The PBL height (PBLH) is referred to as the altitude from the surface to the top of the PBL and is also known as the PBL depth or thickness. Surface forcing response, drag, turbulence, and vertical mixing are strongly evident here and play a critical role within PBL compared to their importance in the overlying "free atmosphere" (Stull, 1988). The PBLH is a vital parameter in climate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Throughout most of the ocean, areas of higher and lower PBLH correspond. Ding et al (2021) also found similar patterns and a low-bias in the MERRA-2 PBLH over oceans when comparing the MERRA-2 data to AIRS and COSMIC Radio Occultation estimates of PBLH.…”
Section: Threshold Algorithmsupporting
confidence: 59%
“…Throughout most of the ocean, areas of higher and lower PBLH correspond. Ding et al (2021) also found similar patterns and a low-bias in the MERRA-2 PBLH over oceans when comparing the MERRA-2 data to AIRS and COSMIC Radio Occultation estimates of PBLH.…”
Section: Threshold Algorithmsupporting
confidence: 59%
“…As a result, PBLH has an impact on temperature and near-surface winds. PBLH retrievals from various sources of satellite measurements were intercompared in recent research ( Ding et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…We also evaluated PBLH from the retrievals in comparison to ECMWF for the same land, daytime test profiles. While many approaches can be used to evaluate PBLH and the best choice is typically regime-dependent, we used a vertical gradient approach similar to Seidel et al (Seidel, Ao, & Li, 2010).While relative humidity gradient is one quantity which has previously been used to evaluate PBLH (Ding, Iredell, Theobald, Wei, & Meyer, 2021), we evaluated gradients in both 𝑞 and 𝑇 𝑝𝑜𝑡 individually, as both are useful indicators of the PBL top as illustrated in Figure 1, and both are more directly related to the variables retrieved by the algorithms. We also check PBLH derived from 𝑞 against the PBLH derived from 𝑇 𝑝𝑜𝑡 to confirm whether they are mutually consistent as physically expected.…”
Section: Figure 13: (A) Rms Error As a Function Of Altitude For T And...mentioning
confidence: 99%